Evidence for Two Levels of Intimate Partner Violence and Aggression Among Incarcerated Young Male Violent Offenders - Sjödin, Anna-Kari (International journal of offender therapy and comparative criminology, 2018)
Furthering knowledge of the subset of incarcerated partner violent offenders distinguished by aggression, anger, and hostility is relevant, as these offenders are guilty of the more severe kinds of intimate partner violence (IPV). Our aim was to identify groups with different patterns of IPV among convicted young Swedish male offenders, using data from the Development of Aggressive Antisocial Behavior Study, including 171 young men (18-25 years) convicted of a violent crime. Cluster analysis was used to identify different clusters based on amount and severity of IPV in combination with measures of anger, hostility, aggression, and psychopathic personality traits. The results point to an association between antisocial development, criminal history, the severity of current crime, and measures of aggression, hostility, and partner abuse. The cluster defined by higher levels of partner abuse and aggression was significantly associated with early onset conduct disorder.